Efficacy Of Rodenticides In Controlling Major Rat Species Of Oil Palm, Rattus Tiomanicus (Miller) In Sungkai, Perak - Noh, Ariff Ateed Bin Mohd (2022)
The efficacy of different types of rodenticides in controlling major rat species of oil palm, Rattus tiomanicus (Miller) was carried out in a comparative study among six types of rodenticide baits selected from first-generation anticoagulants: coumatetralyl, chlorophacinone and warfarin, second-generation anticoagulants: brodifacoum and flocoumafen, and non-anticoagulant rodenticide cholecalciferol. The study of the efficacy of selected rodenticide baits was conducted in both laboratory and field assessments. In the laboratory study, no-choice feeding study showed that flocoumafen bait was the most effective in this study compared to other treatments by recording complete mortality against R. tiomanicus. Warfarin bait recorded the lowest efficacy result in this study against R. tiomanicus by only recording 46.07% mortality. Choice feeding study results showed that flocoumafen bait recorded the highest mortality compared to other treatments at 55% while the least efficacy was recorded by warfarin at only 10% mortality. In addition, flocoumafen bait recorded highest bait acceptance at 30.50% and the most palatable bait at 1:2 compared to other treatment baits. In this evaluation, warfarin was the least effective (8.98%) and the least palatable bait (1:7) of the rats compared to other treatment baits. All treatment baits managed to control oil palm fresh rat damages below the threshold level (5%) except warfarin bait. The final result showed that fresh rat damages in treated areas dropped below the threshold level compared to the damages recorded earlier in pre-treatment. Warfarin bait recorded the least effective result, which was above the threshold level compared to other treatment baits.